(untitled) - Scott, Ronald E. (London, 1960)
Contents: Chapter 15: Introduction to Sine Waves and the Frequency Domain Chapter 16: Frequency - Domain Networks Chapter 17: Mutual Inductance, Unity - Coupled Coils, and Transformers Chapter 18: Magnitude and Phase Response Curves Chapter 19: Power and Energy in Alternating- currenr Circuits Chapter 20: Signal Analysis in the Frequency Domain Chapter 21. Network Response to Complex Waves of Excitation Chapter 22. Problems Solved by Laplace Transforms Chapter 23. Power and Energy Relationships in Networks Excited by Arbittrary Functions
Keywords: Electric circuits, Linear,Mạch tuyến tính